2020
DOI: 10.1038/s41392-020-00349-7
|View full text |Cite
|
Sign up to set email alerts
|

Methionine metabolism in chronic liver diseases: an update on molecular mechanism and therapeutic implication

Abstract: As one of the bicyclic metabolic pathways of one-carbon metabolism, methionine metabolism is the pivot linking the folate cycle to the transsulfuration pathway. In addition to being a precursor for glutathione synthesis, and the principal methyl donor for nucleic acid, phospholipid, histone, biogenic amine, and protein methylation, methionine metabolites can participate in polyamine synthesis. Methionine metabolism disorder can aggravate the damage in the pathological state of a disease. In the occurrence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 165 publications
(255 reference statements)
4
33
0
Order By: Relevance
“…34 In human medicine, controversy exist as to whether methionine supplementation is useful in patients with chronic liver disease. 35 Our findings suggest that the liver-supportive diet used might not be ideally balanced in terms of amino acids for dogs with portosystemic shunting. A double-blind cross-over study found that clinical signs of HE significantly improved in dogs with PSS that received a diet based on soy instead of meat protein.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…34 In human medicine, controversy exist as to whether methionine supplementation is useful in patients with chronic liver disease. 35 Our findings suggest that the liver-supportive diet used might not be ideally balanced in terms of amino acids for dogs with portosystemic shunting. A double-blind cross-over study found that clinical signs of HE significantly improved in dogs with PSS that received a diet based on soy instead of meat protein.…”
Section: Discussionmentioning
confidence: 80%
“…A double-blind cross-over study found that clinical signs of HE significantly improved in dogs with PSS that received a diet based on soy instead of meat protein. 35 Yet, the BCAA-to-AAA ratio of the soy-based diet was only 2.05 compared to 2.30 for the meat-based diet. Despite a lower BCAA-to-AAA ratio in the food, improved HE scores in that study were attributed to the fact that vegetable proteins are highly digestible leading to a higher absorption of amino acids in the small intestine and subsequently less nitrogen reaching the colon.…”
Section: Discussionmentioning
confidence: 94%
“…[methyl- 2 H 3 ] methionine : Methionine is an essential amino acid that has an important role in many cellular functions. In addition to being an essential component in the initiation of protein synthesis, methionine can also take part in (1) the methionine cycle, converted to the important methyl donor s-adenosylmethionine (SAM), (2) polyamine synthesis, (3) folate metabolism, and (4) glutathione synthesis via the trans-sulfuration pathway [ 127 , 128 ]. London et al administered L-[methyl- 2 H 3 ] methionine in excess to rodents in order to investigate its hepatic metabolism in particular its conversion to [methyl- 2 H 3 ] sarcosine, clearance of L-[methyl- 2 H 3 ] methionine, formation of N-trimethyl-labeled metabolites, and enrichment of water with deuterium [ 129 ].…”
Section: Probes For Dmimentioning
confidence: 99%
“…Methionine metabolism and methyltransferases have important roles in regulating health and lifespan 39 , and defects in the methionine-homocysteine cycle have been linked with a large number of pathological conditions [40][41][42] . Therefore, the methionine-homocysteine cycle has become an important intervention point for improving lifespan and health 39,[42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%